2019
DOI: 10.1111/ajag.12674
|View full text |Cite
|
Sign up to set email alerts
|

Alternative staffing structures in a clustered domestic model of residential aged care in Australia

Abstract: Objective: A clustered domestic model of residential aged care has been associated with better consumer-rated quality of care. Our objective was to examine differences in staffing structures between clustered domestic and standard models. Methods: A cross-sectional study involving 541 individuals living in 17 Australian not-for-profit residential aged care homes. Results: Four of the homes offered dementia-specific clustered domestic models of care with higher personal care attendant (PCA) hours-per-resident-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…However, this difference did not seem to negatively impact level or quality of care because residents of the small home model received slightly more care hours per resident per day than residents in the traditional LTC homes (mean = 2.66 [SD = 0.35] vs. mean = 2.58 [SD = 0.44]; P = 0.006). 42 This finding is in line with another study that reported that small house model staff outperformed staff from larger homes, spent 3 times to 6 times more time in personal care situations, and spent significantly more time in task-oriented interactions than traditional home staff. 26…”
Section: Organizational Structuresupporting
confidence: 89%
See 3 more Smart Citations
“…However, this difference did not seem to negatively impact level or quality of care because residents of the small home model received slightly more care hours per resident per day than residents in the traditional LTC homes (mean = 2.66 [SD = 0.35] vs. mean = 2.58 [SD = 0.44]; P = 0.006). 42 This finding is in line with another study that reported that small house model staff outperformed staff from larger homes, spent 3 times to 6 times more time in personal care situations, and spent significantly more time in task-oriented interactions than traditional home staff. 26…”
Section: Organizational Structuresupporting
confidence: 89%
“…35,40,41 In the 2 studies that reported on wages -conducted in the US and Australia -wages did not differ significantly between the small house models and the comparator traditional LTC homes. 32,42 Although the homes based on the small house model are staffed with the same assortment of caregivers (i.e., job descriptors), numerous studies reported that a higher proportion of staff hours in the smaller homes tended to be from those in positions requiring less formal training (i.e., a higher proportion of certified nursing assistants providing care as opposed to registered nurses). 14,32,[42][43][44] In a direct comparison of 4 Australian domestic-clustered homes with 13 traditional LTC facilities, Harrison et al (2018) found that care providers in homes based on the small house model spent significantly fewer hours per resident per day compared with the traditional model: degree-or diploma-trained nurses (mean = 0.23 [SD = 0.10] vs. mean = 0.85 [SD = 0.17]; P < 0.01) and allied health staff (mean = 0.02 [SD = 0.01] vs. mean = 0.15 [SD = 0.1]; P = 0.042).…”
Section: Organizational Structurementioning
confidence: 99%
See 2 more Smart Citations
“…As well as having design differences, including housing for smaller groups of residents and independent access to outdoors, the home-like model of care incorporates a different staffing structure, with higher direct care hours and investment in staff training [35]. Dutch studies have also indicated that small-scale living environments have the potential to benefit residents and that factors other than just the physical design, in particular staffing factors, have a role in optimal use of outdoor areas [16].…”
Section: Discussionmentioning
confidence: 99%